Technical efficiency, mergers and acquisitions of ASEAN based telecommunication companies / Wan Anisabanum Salleh - Salleh, Wan Anisabanum (2017)
Multiple mergers and acquisitions (M&A) in a period of years may give rise to the accumulation of organizational inefficiencies. In light of the foregoing, this study was done by taking into account the consequences of multiple M&A activities undergone by the telecommunication companies in the Association of the Southeast Asian Nations (ASEAN) using year-by-year projections. Instead of using traditional financial ratios from accounting statements such as return on assets for measuring performance, this study intends to provide a broad view of the effects of M&A and asset utilisation on technical efficiency (TE). The study employed the Data Envelopment Analysis approach which calculated the TE, using the total asset of ASEAN based telecommunication companies, from the period of 2000 to 2011. Subsequently, regression analysis was employed to examine the factors that influenced the TE of the companies. Thus, this study was done by taking into account the consequences of M&A sequencing, M&A intensity and size of companies towards TE. In addition, the study investigated the relationship between gross domestic product (GDP) and TE. Then, this study evaluated the impact of M&A events on TE. The final investigation was done to see the impact of different income levels of the countries toward TE. The empirical findings indicated that a downward trend is registered for the TE of the companies concerned. Meanwhile, the sequence of M&A, companies' size and GDP were significantly negative in relation to TE. Further findings focusing on M&A events such as post M&A, demonstrated that coefficients of post-three year and post-four year M&A have significantly negative relationship with TE. Finally, the results of analysing the impact of high income and lowermiddle-income countries have resulted significantly positive and negative relationship to TE, respectively. The limitations of this study were scarcity of data, which were mainly collected from Osiris because very limited companies have involved themselves in multiple M&A. Hence, the data of the 264 companies that appeared for over the 12 year period, were treated as 2489 decision making units (DMUs) with unbalanced data. Notwithstanding the limitations, the findings of this study provide valuable insight into the efficiency of companies which would enable the formulation of a future approach towards strategic sequence of M&A, so that higher relative efficiencies can be realized. These findings might also be helpful to the relevant authorities in coming up with useful guidelines for companies contemplating multiple M&A. The thesis ends with several recommendations that may be adopted by ASEAN countries to improve their current governing laws, such as merger control under the Competition Law, to sustain the relative efficiency of companies.